An Analysis of the Characteristics, Needs And Motivations of Students who study through ODL in Zimbabwe - Mupindu, Wiseman Nil (Advances in Social Sciences Research Journal, 2015)
Abstract The study sought to establish the characteristics, needs and motivations of the Open and Distance Learner in Zimbabwe. The study was premised on the notion that understanding the customer is the foundation of the delivery of quality services. The study employed the case study method which falls within the qualitative research methodology. The study also utilized some quantitative techniques on data presentation and analysis. Data were generated through a questionnaire survey, focus group discussions, observation and document survey. The use of several data generation techniques assisted to enhance rigour, trustworthiness and credibility of the study. The study revealed that learners were motivated to study through ODL because of the need for promotion, upgrading, securing alternative employment, job security and the need to study while at the same time being with the family or at the workplace. Financing education was reported to be a major challenge for the ODL learner due to several dependants and other family responsibilities. The study concluded that ODL practitioners had inadequate information on the key characteristics, needs and motivations of the ODL learner. The study also concluded that the needs, motivations and characteristics of the ODL learners had a major effect on their service expectations. The study recommends that the University should include, in its students’ records, vital information on the characteristics, needs and motivations of the ODL learner. The study also recommends that the University should align its service strategy with the service expectations of and environmental constraints confronting the ODL learner.